2017
DOI: 10.1002/slct.201702176
|View full text |Cite
|
Sign up to set email alerts
|

Tetrafluoroborate and Hexafluorophosphate Ions are not Interchangeable: A Density Functional Theory Comparison of Hydrogen Bonding

Abstract: Due to their similarities in charge and composition, the tetrafluoroborate (BF 4 À ) and hexafluorophosphate (PF 6 À ) ions are often used interchangeably in chemical studies. As a result, the ability of BF 4 À , but not PF 6 À , to inhibit the hydrolysis of alkyl thiosulfates in non-aqueous solution was surprising. This divergence in reactivity may reflect differences in the ability of these ions to form strong hydrogen bonds to hydronium ion, which catalyzes the hydrolysis, and prompted the current computati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The literature suggests that the PF 6 − counterion is a weaker hydrogen bond acceptor than BF 4 − . 34 This is supported by the pK BHX values of PF 6…”
Section: ■ Results and Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The literature suggests that the PF 6 − counterion is a weaker hydrogen bond acceptor than BF 4 − . 34 This is supported by the pK BHX values of PF 6…”
Section: ■ Results and Discussionmentioning
confidence: 70%
“…PF 6 – was chosen over the ClO 4 – anion which is more similar in size to the BF 4 – anion due to safety considerations. The literature suggests that the PF 6 – counterion is a weaker hydrogen bond acceptor than BF 4 – . This is supported by the p K BHX values of PF 6 – and BF 4 – , which are 1.77 ± 0.15 and 2.24 ± 0.10 respectively .…”
Section: Resultsmentioning
confidence: 77%
“…The hypothesis that the breaking (or rearranging) of hydrogen bonds within the crystal lattice is responsible for the thermochromic transition can be inferred through analysis of the relative hydrogen bond strengths associated with each anion of the known thermochromic materials in the dieten -ligand family (summarized in Table ). Although not a direct comparison of the M 2+ dieten complexes, ab initio calculations of relative hydrogen bond strengths from several studies show anion–water hydrogen bond energies in the range of 4–7 kcal/mol for BF 4 – , 12–15 kcal/mol for ClO 4 – , and 15–21 kcal/mol for NO 3 – . Accordingly, the thermochromic transition temperatures of the [M­( dieten ) 2 ]­(X) 2 materials (where M = Cu, Ni and X = BF 4 – , ClO 4 – , NO 3 – ) increase in the order of increasing relative hydrogen bond strength . [Ni­( dieten ) 2 ]­(NO 3 ) 2 does not have an observable transition below the decomposition temperature of the material, which is consistent with the predictive criteria just outlined .…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the anion and cation’s ability to form hydrogen bonds determines the solubility of water in imidazolium-based ILs, and that the anion structure influences the hydrogen bond strength with water . Although [BF 4 ] − and [PF 6 ] − anions have similar charge and composition, the electrons are more localized on the F atoms of [BF 4 ] − than of [PF 6 ] − , leading to the stronger hydrogen bonding within the complexes formed by [BF 4 ] − with water and H 3 O + . Indeed, DVS measurements have shown that [C 4 C 1 im]­[PF 6 ] adsorbs less water than [C 4 C 1 im]­[BF 4 ] (∼2.3 wt % vs 38 wt % at P / P 0 = 95%, or 1.0 wt % vs 3.9 wt % at P / P 0 = 60%, always under room-temperature conditions) .…”
Section: Results and Discussionmentioning
confidence: 99%